A comparative study of postpartum hemorrhage severity in mothers with and without methylergometrine administration in normal labor - Ahmad Alwan Tsany; Aria Wibawa (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: Postpartum hemorrhage is a major cause of maternal morbidity and mortality, particularly in vaginal delivery, with uterine atony as the most common etiology. Therefore, the administration of uterotonic agents during the third stage of labor plays an important role in preventing postpartum hemorrhage. Methylergometrine is still widely used; however, data regarding its effect on the severity of postpartum hemorrhage in Indonesia remain limited. Purpose: To compare the severity of postpartum hemorrhage among women with normal vaginal delivery who received and did not receive methylergometrine at RSUD Dr. Moewardi Surakarta. Method: This study was an observational analytic study with a retrospective cohort design using secondary data from medical records. A total of 92 women with normal vaginal delivery who experienced primary postpartum hemorrhage during the period 2022–2024 were included and divided into groups receiving and not receiving methylergometrine. The severity of postpartum hemorrhage was classified into mild–moderate and severe. Data were analyzed using univariate and bivariate analyses with the Fisher’s exact test at a significance level of p < 0.05. Results: All women who received methylergometrine experienced mild–moderate postpartum hemorrhage, whereas 9.5% of severe postpartum hemorrhage cases were found in the group that did not receive methylergometrine. There was a significant association between methylergometrine administration and the severity of postpartum hemorrhage (p = 0.026), with an odds ratio of 0.905 (95% CI: 0.820–0.998). Conclusion: Methylergometrine administration was significantly associated with a reduced severity of postpartum hemorrhage in women with normal vaginal delivery.